Qinghaosu, the antimalarial of chinese materia medica - Legua-Leiva , Pedro (2019)
Presents the story of how a plant of ancient Chinese medicine, qinghaosu, has provided medical science of an effective antimalarial substance: artemisinin. This is a modern analogy of what happened with quinine from the bark of Cinchona.